P-184 Initiating a hospice inpatient diuresis service. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Kasznicka, Beata; Chumbley, Karen; Tempest, Emma
Abstract : Background: Heart failure is a progressive, highly symptomatic condition (McIlvennan & Allen, 2016), characterised by weakening of the heart muscle, resulting in the inability to maintain an adequate cardiac output. The impact of heart failure is significant with both patients and families requiring much support. One of the typical symptoms is peripheral and pulmonary oedema, which has huge impact on quality of life. This can be managed via parenteral administration of diuretics. The need for a service offering diuresis in a non-acute setting was identified via multidisciplinary team meetings involving the hospice and the community heart failure team. Aim: To create a safe and effective diuresis service within the hospice inpatient unit for people with advanced heart failure. Method: The diuresis service was commenced after reviewing current literature and exploring already established services. We developed a policy and procedure for the administration of subcutaneous Furosemide within the hospice setting. This was then reviewed by the medical and nursing team within the hospice to ensure it was both safe and feasible. Results: Since the inception of this service in July 2018, St Helena has offered diuresis to 19 patients. An audit showed that we are following our guideline. Conclusion: It is feasible to establish a diuresis service using the administration of subcutaneous Furosemide in a hospice setting. The introduction of this hospice-led service has extended the possibility of diuresis for patients who are not fit for hospital admission and offered the choice of place of care for patients diagnosed with advanced heart failure. The next step is to evaluate the input of this service on patients' symptoms and quality of life.